Study of Facial Nerve Function Following Retromandibular Open Reduction of Mandibular Condylar Fracture - Muhammad Ahsan Bhatti, Kamal Muhammad Mustafa, Mohammad Umar, Atif Iqbal Butt, Sadaf Shamshad, Rida Zulfiqar (Pakistan Journal of Medical & Health Sciences, 2023)
At least 1/3rd (26–40%) of all mandibular fractures occur in the condylar region, making it one of the most common fracture sites. They can further lead to morphological & functional damage when undetected or poorly managed. Condylar fractures that are misdiagnosed or improperly treated can cause substantial functional impairment, such as malocclusion, decreased mouth opening due to jaw deviation, and restricted lateral mandibular motions. Objectives: The aim of the study was to examine facial nerve function following retromandibular trans parotid ORIF for mandibular sub-condylar fractures. Methodology: After receiving the necessary ethical approval, 50 patients who presented with unilateral condylar fractures, sub condylar fractures (36), & neck fractures (14) (Ellis classification)5 were chosen. All of the research participants, who underwent open reduction using a retromandibular technique, provided informed consent. Results: All 50 patients were assessed and no patients were excluded. The healing went well, and no one experienced significant scarring or hardware infection. 7 (14%) individuals experienced transient buccal branch weakness, while 2 (4%) experienced transient zygomatic branch dimness Keywords: Condylar fracture, Open reduction, Retromandibular approach, Anatomical reduction